2018
DOI: 10.1159/000493195
|View full text |Cite
|
Sign up to set email alerts
|

Relative Factors Analysis of Imatinib Trough Concentration in Chinese Patients with Gastrointestinal Stromal Tumor

Abstract: Aims: Imatinib plasma trough levels (IM Cmin) have been reported to have a considerable clinical impact in patients with gastrointestinal stromal tumors (GISTs). We therefore have investigated the factors affecting IM plasma concentration in Chinese GIST patients. Methods: IM Cmin in 190 patients with GIST who were taking IM were measured. Results: In patients treated with IM 300 mg/day (n = 16), 400 mg/day (n = 168), and > 400 mg/day (500: n = 1, 600: n = 5), IM Cmin was 1,564… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…Another reason for the higher C min at 600 mg daily in our study may be that we divided the 600 mg daily dose into 300 mg twice daily to minimize gastrointestinal reactions, whereas the B2222 trial used a once daily dose of 600 mg daily. Consistent with previous reports of patients with GIST and chronic myeloid leukemia, age, body weight, plasma albumin level, and creatinine clearance were significant covariates for imatinib plasma exposure; and higher values were correlated with a lower imatinib C min , except for age. However, the overall effect of these covariates on imatinib plasma exposure was small, and there may be other influencing factors, including food intake, major gastric resection, and cytochrome P450 and drug transporter sequence variants …”
Section: Discussionsupporting
confidence: 89%
“…Another reason for the higher C min at 600 mg daily in our study may be that we divided the 600 mg daily dose into 300 mg twice daily to minimize gastrointestinal reactions, whereas the B2222 trial used a once daily dose of 600 mg daily. Consistent with previous reports of patients with GIST and chronic myeloid leukemia, age, body weight, plasma albumin level, and creatinine clearance were significant covariates for imatinib plasma exposure; and higher values were correlated with a lower imatinib C min , except for age. However, the overall effect of these covariates on imatinib plasma exposure was small, and there may be other influencing factors, including food intake, major gastric resection, and cytochrome P450 and drug transporter sequence variants …”
Section: Discussionsupporting
confidence: 89%
“…Major gastrectomy has been shown to significantly lower imatinib exposure . However, no significant correlation between the use of proton pump inhibitors and imatinib exposure was found …”
Section: Methodsmentioning
confidence: 99%
“…Major gastrectomy has been shown to significantly lower imatinib exposure. 110,111 However, no significant correlation between the use of proton pump inhibitors and imatinib exposure was found. 14 Conflicting results are reported for the influence of renal function on imatinib pharmacokinetics, with some studies describing higher imatinib AUCs in patients with renal dysfunction, while other studies describe no correlation.…”
Section: Explaining Interpatient Variability In Pharmacokinetics 2mentioning
confidence: 97%
“…Wu and coworkers (Wu et al, 2018) found significantly higher steady-state concentrations in females (1,680.79 ± 669.03 ng/ml, n 86) than those in males (1,353.94 ± 492.89 ng/ml, n 82; p < 0.01) after the administration of a 400 mg/d dose of IM. Another study (Koo et al, 2015) on 187 females and 122 males in Korea also demonstrated a significant correlation between the trough levels of IM with sex (p 0.010).…”
Section: Gendermentioning
confidence: 93%
“…The outcome from Wu et al (2018) for the effects of dosage on plasma concentrations demonstrated that IM was administered at doses of 300 mg/d (n 16), 400 mg/d (n 168), and >400 mg/d [500 mg/d (n 1) and 600 mg/d (n 5)] based on clinical diagnoses. The C min levels were 1,564.5 ± 596.15 and 2,540.31 ± 1,298.14 ng/ml in patients treated with 300 mg/d and >400 mg/d of IM, respectively, which were significantly different from the C min levels after a dose of 400 mg/d (p 0.033).…”
Section: Dosagementioning
confidence: 99%